Dynamics Of Human Resource Management In Improving Worker Productivity And Welfare In The Digital Era In Indonesia - Syamsu Rijal; Muhlis (International Journal of Business and Quality Research, 2025)
In this digital era, HR management is key to improving employee productivity and well being. Digital transformation requires organizations to adapt not only in business processes but also in workforce management. This includes the implementation of information technology, process automation, and more flexible work approaches. This study adopted a literature review method to explore how HR management can optimize employee productivity and well-being through digital innovation. The results show that utilizing technology in HR management processes can increase work efficiency. However, this also carries the risk of causing technostress, which can negatively impact employee mental well-being. Therefore, a management strategy that balances digital efficiency and employee emotional well-being is needed. This can be achieved through stress management training, mental health support, and the development of a work culture that supports work-life balance.